Comparative Study of Evaluation of Efficacy and Safety of Combination of Erythromycin and Benzyl Peroxide with Benzyl Peroxide alone in the Treatment of Acne Vulgaris - Yeasmin, Monira; Islam, AZM Maidul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Objective: Acne vulgaris is the disease of the teenagers as 90% of them being affected. So many treatment modalities are there - systemic , topical and physical . Among them topical therapy is the main stay of treatment. Our study was to determine the efficacy and safety of combination of erythromycin/benzyl peroxide compared with benzyl peroxide alone in the treatment of mild to moderate acne. Method: Patients attended in a Charity Foundation were enrolled for the study after fulfilling the criteria. Among total 50 patients 25 were selected for group A and another 25 for group B.. Group A were treated with 3% erythromycin and 5% Benzyl peroxide combination and GroupB with 5% Benzyl peroxide only. Total acne lesions were counted at base line and after 4 , 8 and 12 weeks of follow up. Reduction of total no of lesions were seen and analyzed. Result: At baseline mean of total acne score was 33.60 ± 5.98 and 33.53 ± 5.68 in group A and B (p=0.965). After 12 week it was 2.27 ± 1.08 and 6.27 ± 1.57 respectively in group A and B (p=0.001). Percent reduction of acne severity from base line to final follow up was 93.24 ± 3.11 in group A and 81.17 ± 4.22 in group B (p=0.001). So we can see better reduction of lesion count in Group A than Group B. Conclusion: We conclude that Group A is safer and more effective than that of Group B. So the combination of Benzyl peroxide and erythromycin is better than Benzyl peroxide alone. J Bangladesh Coll Phys Surg 2017; 35(4): 174-178